Bacteriemia por Elizabethkingia Meningoseptica en un adulto mayor. Reporte de caso - Óscar Fabián Rojas-Gómez; Sergio Andrés Hernández-Gutiérrez; Angy Estefanía Díaz-Vidales; Álvaro Leal-Rodríguez (Case Reports, 2025)
Resumen